2016
DOI: 10.1038/srep23565
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic analysis of mushroom polysaccharide-treated HepG2 cells

Abstract: The anti-tumor properties of fungal polysaccharides have gained significant recognition in Asia and tropical America. In this study, the differential expression of proteins in normal HepG2 cells and those treated with polysaccharides that had been isolated from Phellinus linteus (PL), Ganoderma lucidum (GL) and Auricularia auricula (AA) was investigated. Using two-dimensional electrophoresis (2DE), a total of 104 protein spots were determined to be overexpressed in these cells compared with noncancerous region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 44 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…In addition, they also resulted in the activation of mitochondrial-mediated apoptosis and G 1 and/or S phase arrest in HepG2 cells. After a few years, the same research group, in one of their recent studies 59 on proteomic analysis of HepG2 cells treated with mushroom polysaccharide, revealed the differential expression of 59 proteins identified through MALDI-TOF-MS, where DJ-1 and 14-3-3 were the key proteins identified as a result of Protein-Protein interaction analysis. DJ-1 is a novel oncogene product that has been reported to negatively regulate the PTEN activity.…”
Section: Targeting the Pi3k/akt Signaling Pathway In Cancermentioning
confidence: 99%
“…In addition, they also resulted in the activation of mitochondrial-mediated apoptosis and G 1 and/or S phase arrest in HepG2 cells. After a few years, the same research group, in one of their recent studies 59 on proteomic analysis of HepG2 cells treated with mushroom polysaccharide, revealed the differential expression of 59 proteins identified through MALDI-TOF-MS, where DJ-1 and 14-3-3 were the key proteins identified as a result of Protein-Protein interaction analysis. DJ-1 is a novel oncogene product that has been reported to negatively regulate the PTEN activity.…”
Section: Targeting the Pi3k/akt Signaling Pathway In Cancermentioning
confidence: 99%
“…In recent years, many researchers have begun to seek natural compounds due to their anti-inflammatory activities and nontoxicity12. It was well known that natural polysaccharides exhibited a wide range of biological activities, especially the antioxidant and immunoregulatory activities1314. Several polysaccharides were found to have good anti-inflammatory and hepatic activity1516, however, limited by low yield and low activity, it is thus necessary to find a way to strengthen the bioactivities of polysaccharides17.…”
mentioning
confidence: 99%
“…Although we first provide the differential protein expression profile of HepG2 cell in response to TNFα, proteomic analysis of HepG2 in response to other stimuli such as mushroom polysaccharide 14 or in comparison to human hepatocyte 15 has been reported. Among these proteomic analyses for HepG2, cytoskeletal components, HSPs/chaperones, 14-3-3 family, oxidoreduction-associating proteins, and energy metabolism-associating proteins have been widely identified and investigated.…”
Section: Discussionmentioning
confidence: 99%